Moving beyond (non-)compliance: the customization of European Union policies in 27 countries - Thomann, Eva; Zhelyazkova, Asya (Journal of European public policy, 2017)
Europeanization research often neglects that the implementation of European Union (EU) policy results in diverse national outcomes, even if member states comply with EU law. Such fine-grained Europeanization patterns have been explored as 'gold-plating' and 'customization'. This contribution builds and expands on this research to propose a general conceptualization and measurement of customization as the changes that provisions of EU Directives undergo in their regulatory density and restrictiveness during legal transposition. Using unique data on the customization of EU directive provisions from two policy areas in 27 countries, our empirical analysis reveals distinct changes in density and restrictiveness, pronounced policy-specific and state-level customization patterns. The findings illustrate how national customization strategies often follow specific EU regulatory logics in different integration contexts. We outline implications for future research on the causes and consequences of the inherent diversity of EU implementation regarding dimensions of customization, issues of legitimacy and effectiveness.
Gesehen am 26.04.2018